PENGARUH DIVERSIFIKASI PENDAPATAN, BOPO DAN CARTERHADAP PROFITABILITAS PERBANKAN SELAMA PANDEMI COVID-19 - Bahtiar Fitanto; Sofianingsih, Reni (Contemporary Studies in Economic, Finance and Banking, 2022)
The Covid-19 pandemic has disrupted the pace of Indonesia's economic growth. The policy of lowering interest rates in the context of the national economic recovery as well as slowing credit disbursement resulted in a decline in the NIM of the banking system. Therefore, banks are trying to find new sources of income other than interest income sources, namely through diversification. In addition to income diversification, operational efficiency and management of capital aspects are also very important factors that can affect bank conditions during the Covid-19 pandemic. This study aims to analyze the effect of income diversification (DIVPEN), operational efficiency (BOPO) and capital adequacy ratio (CAR) on banking profitability proxied by ROA during the Covid-19 pandemic at KBMI bank 4. Data analysis method used in this study namely panel data regression analysis with the best model results, namely FEM (Fixed Effect Model). The results show that income diversification has a positive and significant effect on ROA, BOPO has a negative and significant effect on ROA and CAR has no effect on bank profitability proxied by RPA during the Covid-19 pandemic.